Molecular characterization of human respiratory syncytial virus in Mexico (season 2023–2024) through whole-genome sequencing - Evelyn Rivera-Toledo; Fidencio Mejıa-Nepomuceno; Enrique Mendoza-Ramırez; America Vera-Jimenez; Eduardo Becerril-Vargas; Victor Hugo Ahumada-Topete; Manuel Castillejos-Lopez; Francisco Bernardo Perez-Orozco; Geovanni Benitez; Miguel Ángel Salazar-Lezama; Josue Daniel Cadeza-Aguilar; Emma Garcia-Colin; et al. (Scientific Reports)
Abstract Human respiratory syncytial virus (hRSV) is a one of major cause of severe acute respiratory infection (SARI) in young children and the elderly. Because genomic surveillance of hRSV is essential to understand viral evolution and the genetic variation that may affect transmissibility and pathogenicity, we sequenced complete genomes of hRSV-A and B from season 2023–2024, isolated from pediatric and adult patients with SARI. One hundred pediatrics and 43 hospitalized adult and 14 non-hospitalized adult patients testing positive for hRSV were enrolled. Libraries of whole hRSV genomes were generated and sequenced on a MiSeq platform. Phylogenetic analysis and maximum likelihood trees were constructed with the 64 hRSV-A and 29 hRSV-B sequences obtained in our study. Additionally, we analyzed the list of non-synonymous substitutions and their frequencies for each of the eleven viral proteins. hRSV-A was prevalent (68%) and principally affected children under five years old. The hRSV-A isolates belonged to the A.D lineage with sub-lineages A.D.1.5, A.D.1.8, A.D.3, and A.D.5.2 observed. The hRSV-B subgroup was less diverse since the dominant sub-lineage was B.D.E.1. Amino acid substitutions per viral isolate for each of the eleven viral proteins indicated higher variability in hRSV-A compared to hRSV-B. As expected, we observed a high diversity of substitutions in proteins G, F and L. Multiple lineages and a high mutation rate were identified in hRSV-A during winter season 2023–2024 in Mexico. The increasing availability of whole hRSV genome sequences will enhance the surveillance of specific genetic substitutions, contributing to a better understanding of viral evolution and the effectiveness of prophylactic and diagnostic strategies.